Demand analysis for cereal crops in Ethiopia - Wogayehu Abele; Malefiya Ebabu; Sindie Alemayehu (Наукові горизонти, 2022)
Cereals are common in Ethiopian diets, but the people’s consumption habits are complex, with no single crop dominating. Empirical analysis of cereal crop household demand is required to quantify household responses to cereal crop value changes and individual income changes. A purpose of this study is to assess demand for major cereal crops in Ethiopia using secondary data from Ethiopian Social Economic Survey 2018/19 (ESS) with 1700 households of cereal-growing consumers. This paper utilises descriptive statistics and Almost Ideal Demand System (AIDS) model to estimate demand parameters for major cereal crops. The empirical results showed that crop prices themselves, prices of other crops and demographic factors influence the share of grain expenditure. The estimated income elasticity of all sampled cereals is positive, and the Marshallian (unpaid) price elasticity is elastic while the compensated cross-price elasticity was inelastic. Household response to cereal crop demand decreases as commodity prices rise. Teff was the most price-sensitive commodity and classified as a luxury good because its income elasticity value was greater than one. Wheat, maize, and sorghum were designated as necessities, and all of the cereal crops studied in this work are considered normal goods. According to the study, the magnitude of price elasticity is greater than the expenditure elasticity of cereal crops. This implies that price has a greater influence than income. As a result, price regulation policies would be more effective than income targeting policies. Furthermore, the positive expenditure elasticity suggests that as income rises, so will demand for cereal crops. Policies aimed at increasing income would increase demand for cereals